Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

jenben22

  • 3 years ago

Use the Substitution Method to solve the following system of equations. 2x + y = 3 -3x + 4y = 1 (1, 1) (-1, -1) (1, -1) (-1, 1)

  • This Question is Closed
  1. Grazes
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    Set one of the equations to equal y. Ex. 2x+y = 3 ----> y=-2x+3 Then, you substitute the y in the other equation with your equation set to y. -3x + 4y = 1 ----> -3x + 4[-2x+3] = 1 Then, solve for x

  2. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy